Fatigue Behaviour on MAG and Hybrid Welding : Geometrical and Hardness Analysis - Padín García, Bruno (2013)
Since its inception nearly a century ago, the automotive industry has relied heavily on joining technologies. This industry utilizes a wide array of welding processes, materials, coatings, and designs. Laser welding is an important and highly advanced manufacturing technique in industry. An emerging option is laser hybrid arc welding.On the other hand, fatigue cracking is one of the primary damage mechanisms of structural components.This Master’s Thesis presents an investigation about fatigue behaviour of an automobile beam member from a company in Luleå. A study of influence of two welding methods (MAG Welding and Hybrid Welding) is carried out.This thesis is divided up into three studies: The first one is a theoretical introduction about influence of weld method.Main characteristics, advantages and drawbacks of the weld methods respect mechanical behaviour (focusing on fatigue) are summarized in this part.The second study includes a geometrical analysis of several pieces welded by MAG or Hybrid Laser welding method. This section also shows the results obtained in a hardness tests of both weld methods and the microstructure of these workpieces.Finally, the third one is a brief cost comparison between Mag and Laser Hybrid welding process. Validerat; 20131219 (global_studentproject_submitter)